The house on the gulf - Haddix, Margaret Peterson (New York : Aladdin, 2006)
A sixteen-year-old boy arranges a housesitting job for the summer, but he starts acting strangely after his family moves in, and his sister begins to suspect they are not supposed to be there.
008-012.
Keywords: Housesitting -- Juvenile fiction; Grandparents -- Juvenile fiction; Housesitting -- Fiction; Grandparents -- Fiction; Mystery and detective stories -- Fiction; Florida -- Juvenile fiction; Florida -- Fiction; Mystery fiction